The association between 331A/T polymorphism in the SHH gene and 385G/A polymorphism in the SMO gene and the development of basal cell carcinomas - Sobolewska-Sztychny, Dorota; Narbutt, Joanna; Sobjanek, Michał; Wódz, Karolina; Sieniawska, Joanna; Woźniacka, Anna; Lesiak, Aleksandra (Dermatology Review/Przegląd Dermatologiczny, 2014)
Introduction. Basal cell carcinomas (BCCs) are the most common of all cancers in the Caucasians, and their incidence has been rising in younger populations. BCC usually occurs in sun-exposed body areas, most commonly on the head, neck and upper extremities. Experimental data have shown that the sonic hedgehog pathway may be involved in BCC development, but the mechanism by which activation of the hedgehog pathway leads to carcinogenesis is still not clear. Objective. The aim of the study was to assess the association between 331A/T polymorphism in the SHH gene and 385G/A polymorphism in the SMO gene and the development of basal cell carcinomas. Material and methods. The study group consisted of 142 Caucasians with histopathologically confirmed BCC and 142 healthy volunteers as a control group. All patients were diagnosed and treated in the Department of Dermatology and Venereology in Lodz. Polymorphisms in SHH and SMO genes were assessed by RFLP-PCR. Results. Associations between 331A/T polymorphism in the SHH gene and 385G/A polymorphism in the SMO gene and the development of basal cell carcinomas were found. Additionally, significant differences in genotype distribution of all examined polymorphisms between BCC patients and controls were detected. Conclusions . The sonic hedgehog pathway is implicated in the etiopathogenesis of basal cell carcinoma, the most common human cancer. A better understanding of the molecular background of this pathway might be useful for introduction of new therapeutic methods.